Auditoría tributaria del comisariato Fae Latacunga de la provincia de Cotopaxi período 1º enero al 31 de diciembre del 2010 - Barba Carrasco, Alicia Eugenia (2013)
The application of the Tributary Auditory was made at the Commissary of FAE Latacunga for the 2010 period, with the objective to determine if it’s accomplishing all its obligations stipulate by the SRI, and that our opinion be of help for an effective execution or the tributary declarations. For the development the investigation the actual information given by was checked by the institution with the authority of the manager, which the investigations was made with an inductive, deductive methodology, in the wich applied technics like: interviews and surveys, directed to all who are involved with the development of economical activities of the institution, the same that permitted to obtain information, and for the application of the mentioned tributary auditory. In base of the information obtained we could know of how the tributary declarations was elaborating, finding as the main inconvenience the form of calculation where there exists errors by fault of the countable system.